Elucidation of flavanones, phenols and antioxidant capacity influenced by drying methods from physiologically dropped underutilized Citrus grandis fruits - Kumar, Dinesh; Ladaniya, M. S.; Gurjar, Manju; Mendke, Sachin; Kumar, Sunil; Ghosh, Dilip (Frontiers in Plant Science, 2023)
Nutritional content in citrus fruit is enormous. Citrus grandis (L.) Osbeck is underutilised citrus crop that receives little attention due to the lack of knowledge regarding its nutritional value. Citrus waste disposal poses a problem due to economic and environmental factors. The metabolites found in the dropped fruits of the underutilised citrus species pomelo (Citrus grandis (L.) Osbeck) are largely unknown. Hesperidin varied from 1.22 to 2.83% and 1.08 to 1.16% from 10 mm to 14 mm whereas naringin dominates in fruits measuring 10 mm and 12 mm with 60.61%, 60.77%, and 47.76%, 45.87% in freeze dried (FD) and hot air oven dried (HAOD) samples. According to the results of the antioxidant assays, the highest concentrations of ABTS (3-ethylbenzthiazoline-6-sulfonic acid) and DPPH (2, 2-diphenyl-1-picrylhydrazyl radical) were found in freeze-dried samples, ranging from 9.679 to 10.416 mmol L-1 Trolox and 14.825 to 16.432 mmol L-1 Trolox, respectively. However, the Ferric Reducing Antioxidant Power (FRAP) assay revealed higher content in samples of both FD and HAOD that were 10 mm in size (4.578 mmol L-1 Trolox and 3.730 mmol L-1 Trolox). Total phenol content was measured, and the highest concentrations were found in fruits with a diameter between 10 mm and 18 mm. It ranged from 48.479 to 54.498 mg GAE L-1 in FD samples and from 45.757 to 51.159 mg GAE L-1 in HAOD samples. The smallest fruits, or those that were still in the immature stage, had the highest content. It was found that when the immature dropped fruits were dried by HAOD, the content decreased. At p<0.01 and p<0.05, there was a significant positive correlation between the flavonoids, antioxidants, and total phenols. The results showed that the immature dropped immature fruits of lesser known underutilised citrus sp. Citrus grandis can act as potential source of flavonoids, total phenol concentration, and antioxidant potential. Freeze drying can be recommended to recover the most bioactive substances from physiologically dropped fruits of Citrus grandis for use in the pharmaceutical and nutraceutical sectors. This study will help in reducing the environmental impact caused due to citrus dropped fruits and its responsible management.